2018
DOI: 10.1080/10409238.2018.1488803
|View full text |Cite
|
Sign up to set email alerts
|

SLX4: multitasking to maintain genome stability

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 233 publications
(542 reference statements)
0
40
0
Order By: Relevance
“…Notably, cells synchronized in G1/S phase contain a pool of MUS81-EME1 that does not cofractionate with the rest of the complex on a sucrose gradient (Wyatt et al., 2017), suggesting the existence of functional subcomplexes. In addition to being able to cleave recombination-associated Holliday junctions, SLX4 has also been reported to promote endonucleolytic processing of replication forks (for review see Guervilly and Gaillard, 2018). Although this seems to primarily involve MUS81-EME1 and SLX1, SLX4-promoted fork processing by XPF-ERCC1 was recently reported (Bétous et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, cells synchronized in G1/S phase contain a pool of MUS81-EME1 that does not cofractionate with the rest of the complex on a sucrose gradient (Wyatt et al., 2017), suggesting the existence of functional subcomplexes. In addition to being able to cleave recombination-associated Holliday junctions, SLX4 has also been reported to promote endonucleolytic processing of replication forks (for review see Guervilly and Gaillard, 2018). Although this seems to primarily involve MUS81-EME1 and SLX1, SLX4-promoted fork processing by XPF-ERCC1 was recently reported (Bétous et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Another structure-selective DNA nuclease, the Slx1-Slx4 complex, also contributes to RI removal. The mammalian SLX4 harbors additional domains for binding to MUS81-EME1 and other proteins, gaining additional functions and regulation, which has been nicely summarized in a recent review (Guervilly and Gaillard 2018).…”
Section: Sumoylation Collaborates With Phosphorylation To Regulate Hjmentioning
confidence: 99%
“…In both yeast and humans, DNA damage signaling kinases phosphorylate proteins in homologous recombination (HR)‐directed repair and have been shown to play an important regulatory role. For example, Mec1 phosphorylates Rtt107, Slx4, and Sgs1, all of which are known to play multiple roles in HR‐mediated repair, from the control of resection to the dissolution or resolution of joint chromosome structures (Sarbajna & West, ; Hang & Zhao, ; Cussiol et al , ; Guervilly & Gaillard, ). Recent work from our laboratory has revealed that phosphorylation of these proteins correlates with the ability of cells to suppress GCRs, suggesting that proper control of HR repair is essential for preventing chromosomal rearrangements (Lanz et al , ).…”
Section: Introductionmentioning
confidence: 99%